A method for preparing a high thermal conductivity epoxy resin composite
By using thermal conductivity particles and anhydride curing agent with specific particle size and morphology in the epoxy resin composite, the problems of insufficient thermal conductivity and viscosity brittleness of the epoxy resin composite are solved, and high thermal conductivity and rapid curing are achieved.
Patent Information
- Application Number
- CN202410151141.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-02
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-02-02
AI Technical Summary
The thermal conductivity of existing epoxy resin composites is insufficient, resulting in a decrease in performance of electrical equipment under high thermal conductivity requirements. The addition of a large amount of inorganic powder will lead to an increase in viscosity and increase in brittleness, affecting performance.
By combining different types of thermally conductive particles of specific particle sizes and morphology, such as prismic alumina, sheet boron nitride and nanosilicon nitride, the thermal conductivity of the epoxy resin composite is significantly improved at a lower addition amount. , and use anhydride curing agent to combine with curing accelerator to achieve rapid curing at lower temperatures.
The thermal conductivity of the epoxy resin composite is significantly improved, viscosity and brittle problems are avoided, rapid curing is achieved, and the overall performance of the material is improved.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer composite materials, and in particular relates to a method for preparing a high thermal conductive epoxy resin composite. Background Art
[0002] Epoxy resin composites have excellent adhesion, electrical insulation and corrosion resistance, and are widely used in electrical equipment and other fields. As electrical equipment develops towards large capacity, high power, small size and light weight, the heat generated by electrical equipment during operation increases significantly. If this heat cannot be transferred out in a timely and efficient manner, the continuous accumulation of heat will cause the electrical equipment to heat up, thereby accelerating the aging of dielectric materials, reducing the working efficiency and reliability of electrical equipment, and shortening its service life. The thermal conductivity of general epoxy resin is 0.15-0.50w / mK, which is far from meeting the high thermal conductivity requirements of existing electrical equipment.
[0003] In order to improve the thermal conductivity of epoxy resin, the prior art generally adopts two methods. One is to obtain intrinsic high-heat polymer by changing the molecular structure and segment structure of the material through molecular design, but this method has the problems of complicated preparation process, high difficulty in polymer synthesis and high cost; the second is to add inorganic powder to epoxy resin to improve the thermal conductivity of epoxy resin. Since the more inorganic powder is added, the higher the thermal conductivity of epoxy resin composite is, in order to improve the thermal conductivity of epoxy resin, a large amount of inorganic powder is usually added, but adding too much inorganic powder will cause the viscosity of epoxy resin to increase sharply, and it is impossible to make each material evenly dispersed, thereby affecting the performance of epoxy resin composite. In addition, too much inorganic powder addition will also cause the brittleness of epoxy resin composite to increase, and reduce the anti-cracking performance of epoxy resin. Therefore, how to reduce the amount of inorganic powder under the premise of maintaining high thermal conductivity of epoxy resin composite is a problem to be solved urgently. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a method for preparing a high thermal conductivity epoxy resin composite. The present invention significantly improves the thermal conductivity of the epoxy resin composite at a relatively low addition amount by compounding different types of thermally conductive particles with specific particle sizes and morphologies, and does not cause a sharp increase in the viscosity of the epoxy resin or increase in the brittleness of the epoxy resin composite. In addition, the anhydride curing agent, under the action of a curing accelerator, can quickly cure the epoxy resin at a relatively low temperature.
[0005] The object of the present invention is to provide a method for preparing a high thermal conductivity epoxy resin composite, comprising the following steps:
[0006] S1. 15 to 19 parts by mass of prismatic alumina, 7 to 9 parts by mass of flake boron nitride, 7 to 9 parts by mass of nano silicon nitride, 1 to 3 parts by mass of a silane coupling agent and water are mixed and dried to obtain a modified inorganic powder;
[0007] S2. 100 parts by mass of epoxy resin, 0 to 10 parts by mass of colorant are mixed, heated with stirring, 30 to 40 parts by mass of modified inorganic powder are added in batches, degassed, 30 to 50 parts by mass of anhydride curing agent and 10 to 20 parts by mass of curing accelerator are added, heated and cured to obtain a high thermal conductivity epoxy resin composite;
[0008] The prismatic aluminum oxide has an edge length of 1 to 15 μm and a bottom side length of 100 to 500 nm. The prismatic aluminum oxide is filled in a staggered manner in the pores. The diameter of the flake boron nitride is 20 to 100 nm. The diameter of the nano silicon nitride is 10 to 20 nm.
[0009] Preferably, in S1, the silane coupling agent includes at least one of KH-570, KH-550, KH-560, and KH-590.
[0010] Preferably, in S1, the drying temperature is 85-90° C. and the drying time is 3-5 hours.
[0011] More preferably, in S1, the drying temperature is 90°C and the drying time is 3 hours.
[0012] Preferably, in S2, the temperature of the heating and stirring is 90-110°C.
[0013] More preferably, in S2, the temperature of the heating and stirring is 100°C.
[0014] Preferably, in S2, the batching is divided into 3 to 6 batches.
[0015] More preferably, in S2, the batching is divided into 5 batches.
[0016] Preferably, in S2, the degassing temperature is 130-140°C and the pressure is 0.1-0.3 kPa.
[0017] More preferably, in S2, the degassing temperature is 135°C and the pressure is 0.2 kPa.
[0018] Preferably, in S2, the anhydride curing agent includes at least one of hexahydrophthalic anhydride, nadic anhydride, 4-methyltetrahydrophthalic anhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, cyclobutanetetracarboxylic anhydride, 3-methyltetrahydrophthalic anhydride, 4-methylhexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylendomethylenetetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, tetrahydrophthalic anhydride, 4-methyltetrahydrophthalic anhydride, and 3,3'-dithiodipropionic anhydride.
[0019] More preferably, the anhydride curing agent is selected from 3,3'-dithiodipropionic anhydride.
[0020] The use method of epoxy resin is that under the action of curing agent, epoxy ring is opened and cross-linked to form a three-dimensional network structure. The curing agents used for epoxy resin are mainly divided into two categories: one is amine-cured epoxy resin cured by amine curing agent, which is mainly used in wind power generation, anti-corrosion materials, etc.; the other is anhydride-cured epoxy resin cured by anhydride curing agent, which is mainly used in electrical insulation materials. Among them, anhydride is a more commonly used epoxy resin curing agent, mainly including aliphatic anhydride, aromatic anhydride, alicyclic anhydride, heterocyclic anhydride, polyanhydride, etc. However, anhydride curing agents usually have a higher softening point and poor compatibility with epoxy resin. In addition, the composition formed by epoxy resin and anhydride curing agent has poor curing performance, and the mechanical properties of the formed curing agent system are difficult to be satisfactory. Among these curing agents, as curing agents for curing epoxy resin at room temperature, amine curing agents such as diethylenetriamine, triethylenetetramine, polyamides, and tertiary amines are known, but the curing of these curing agents also takes as long as 4 to 7 days. Other curing agents (such as anhydride curing agents) are more difficult to cure at room temperature, generally requiring a curing temperature of 80 to 200°C and a curing time of 0.5 to 6 hours.
[0021] During the experiment, the inventors found that 3,3'-dithiodipropionic anhydride curing agent can quickly cure epoxy resin at a relatively low temperature under the action of a curing accelerator. The possible reason is that the disulfide bond in the 3,3'-dithiodipropionic anhydride curing agent coordinates with the metal of the curing accelerator, so that the curing accelerator greatly promotes the curing effect of the curing agent.
[0022] Preferably, in S2, the colorant includes at least one of carbon black, graphite, scarlet powder, phthalocyanine blue, red iron oxide, green iron oxide, and blue iron oxide.
[0023] Preferably, in S2, the curing accelerator includes at least one of iron acetylacetonate, copper acetylacetonate and zinc acetylacetonate.
[0024] Preferably, in S2, the temperature of the heating and curing is 70 to 120° C., and the time is 0.5 to 5 hours.
[0025] More preferably, in S2, the temperature of the heating and curing is 70° C. and the time is 0.5 hour. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0027] Example 1
[0028] This embodiment provides a method for preparing a high thermal conductivity epoxy resin composite, comprising the following steps:
[0029] S1. 15 parts by mass of prismatic alumina, 7 parts by mass of flake boron nitride, 7 parts by mass of nano-silicon nitride, 1 part by mass of silane coupling agent KH-570 and 2000 parts by mass of water were added to a reaction flask and mixed, dried at 90 ° C for 3 hours, and the water was removed to obtain a modified inorganic powder;
[0030] S2. 100 parts by mass of epoxy resin was added to the reaction flask and stirred, heated to 100 ° C, 30 parts by mass of modified inorganic powder was added in 5 batches, degassed at 135 ° C, 0.2kPa until no bubbles were released, the vacuum was released and the temperature was lowered to 100 ° C, 50 parts by mass of hexahydrophthalic anhydride and 10 parts by mass of acetylacetonate iron were added, heated to 110 ° C, cured for 5 hours, cooled and removed to obtain a high thermal conductivity epoxy resin composite;
[0031] The prismatic aluminum oxide has an edge length of 1 to 15 μm and a bottom side length of 100 to 500 nm. The prismatic aluminum oxide is filled in a staggered manner in the pores. The diameter of the flake boron nitride is 20 to 100 nm. The diameter of the nano silicon nitride is 10 to 20 nm.
[0032] Example 2
[0033] This embodiment provides a method for preparing a high thermal conductivity epoxy resin composite, comprising the following steps:
[0034] S1. 19 parts by mass of prismatic alumina, 9 parts by mass of flake boron nitride, 9 parts by mass of nano-silicon nitride, 3 parts by mass of silane coupling agent KH-570 and 2000 parts by mass of water were added to a reaction flask and mixed, dried at 90 ° C for 3 hours, and the water was removed to obtain a modified inorganic powder;
[0035] S2. 100 parts by mass of epoxy resin was added to the reaction flask and stirred, heated to 100 ° C, 40 parts by mass of modified inorganic powder was added in 5 batches, degassed at 135 ° C, 0.2kPa until no bubbles were released, the vacuum was released and the temperature was lowered to 100 ° C, 30 parts by mass of hexahydrophthalic anhydride and 20 parts by mass of acetylacetonate iron were added, heated to 110 ° C, cured for 5 hours, cooled and removed to obtain a high thermal conductivity epoxy resin composite;
[0036] The prismatic aluminum oxide has an edge length of 1 to 15 μm and a bottom side length of 100 to 500 nm. The prismatic aluminum oxide is filled in a staggered manner in the pores. The diameter of the flake boron nitride is 20 to 100 nm. The diameter of the nano silicon nitride is 10 to 20 nm.
[0037] Example 3
[0038] This embodiment provides a method for preparing a high thermal conductivity epoxy resin composite, comprising the following steps:
[0039] S1. 17 parts by mass of prismatic alumina, 8 parts by mass of flake boron nitride, 8 parts by mass of nano-silicon nitride, 2 parts by mass of silane coupling agent KH-570 and 2000 parts by mass of water were added to a reaction flask and mixed, dried at 90 ° C for 3 hours, and the water was removed to obtain a modified inorganic powder;
[0040] S2. 100 parts by mass of epoxy resin was added to the reaction flask and stirred, heated to 100 ° C, 35 parts by mass of modified inorganic powder was added in 5 batches, degassed at 135 ° C, 0.2kPa until no bubbles were released, the vacuum was released and the temperature was lowered to 100 ° C, 40 parts by mass of hexahydrophthalic anhydride and 15 parts by mass of acetylacetonate iron were added, heated to 110 ° C, cured for 5 hours, cooled and removed to obtain a high thermal conductivity epoxy resin composite;
[0041] The prismatic aluminum oxide has an edge length of 1 to 15 μm and a bottom side length of 100 to 500 nm. The prismatic aluminum oxide is filled in a staggered manner in the pores. The diameter of the flake boron nitride is 20 to 100 nm. The diameter of the nano silicon nitride is 10 to 20 nm.
[0042] Example 4
[0043] This embodiment provides a method for preparing a high thermal conductivity epoxy resin composite, comprising the following steps:
[0044] S1. 17 parts by mass of prismatic alumina, 8 parts by mass of flake boron nitride, 8 parts by mass of nano-silicon nitride, 2 parts by mass of silane coupling agent KH-570 and 2000 parts by mass of water were added to a reaction flask and mixed, dried at 90 ° C for 3 hours, and the water was removed to obtain a modified inorganic powder;
[0045] S2. 100 parts by mass of epoxy resin was added to the reaction flask and stirred, heated to 100 ° C, 35 parts by mass of modified inorganic powder was added in 5 batches, degassed at 135 ° C, 0.2 kPa until no bubbles were released, the vacuum was released and the temperature was lowered to 50 ° C, 40 parts by mass of 3,3'-dithiodipropionic anhydride and 15 parts by mass of acetylacetonate iron were added, heated to 70 ° C, cured for 0.5 hours, cooled and removed to obtain a high thermal conductivity epoxy resin composite;
[0046] The prismatic aluminum oxide has an edge length of 1 to 15 μm and a bottom side length of 100 to 500 nm. The prismatic aluminum oxide is filled in a staggered manner in the pores. The diameter of the flake boron nitride is 20 to 100 nm. The diameter of the nano silicon nitride is 10 to 20 nm.
[0047] Example 5
[0048] This embodiment provides a method for preparing a high thermal conductivity epoxy resin composite, comprising the following steps:
[0049] S1. 17 parts by mass of prismatic alumina, 8 parts by mass of flake boron nitride, 8 parts by mass of nano-silicon nitride, 2 parts by mass of silane coupling agent KH-570 and 2000 parts by mass of water were added to a reaction flask and mixed, dried at 90 ° C for 3 hours, and the water was removed to obtain a modified inorganic powder;
[0050] S2. 100 parts by mass of epoxy resin was added to the reaction flask and stirred, heated to 100 ° C, 35 parts by mass of modified inorganic powder was added in 5 batches, degassed at 135 ° C, 0.2kPa until no bubbles were released, the vacuum was released and the temperature was lowered to 50 ° C, 40 parts by mass of hexahydrophthalic anhydride and 15 parts by mass of acetylacetonate iron were added, heated to 70 ° C, cured for 0.5 hours, cooled and removed to obtain a high thermal conductivity epoxy resin composite;
[0051] The prismatic aluminum oxide has an edge length of 1 to 15 μm and a bottom side length of 100 to 500 nm. The prismatic aluminum oxide is filled in a staggered manner in the pores. The diameter of the flake boron nitride is 20 to 100 nm. The diameter of the nano silicon nitride is 10 to 20 nm.
[0052] Comparative Example 1
[0053] This comparative example provides a method for preparing a high thermal conductivity epoxy resin composite, comprising the following steps:
[0054] S1. 17 parts by mass of flaky aluminum oxide, 8 parts by mass of flaky boron nitride, 8 parts by mass of nano-silicon nitride, 2 parts by mass of silane coupling agent KH-570 and 2000 parts by mass of water were added to a reaction flask and mixed, dried at 90 ° C for 3 hours, and the water was removed to obtain a modified inorganic powder;
[0055] S2. 100 parts by mass of epoxy resin was added to the reaction flask and stirred, heated to 100 ° C, 35 parts by mass of modified inorganic powder was added in 5 batches, degassed at 135 ° C, 0.2kPa until no bubbles were released, the vacuum was released and the temperature was lowered to 100 ° C, 40 parts by mass of hexahydrophthalic anhydride and 15 parts by mass of acetylacetonate iron were added, heated to 110 ° C, cured for 5 hours, cooled and removed to obtain a high thermal conductivity epoxy resin composite;
[0056] The particle size of the flaky aluminum oxide is as follows: D50 is 20 μm to 30 μm; the diameter of the flaky boron nitride is 20 to 100 nm; and the diameter of the nano silicon nitride is 10 to 20 nm.
[0057] Comparative Example 2
[0058] This comparative example provides a method for preparing a high thermal conductivity epoxy resin composite, comprising the following steps:
[0059] S1. 17 parts by mass of prismatic alumina, 8 parts by mass of flake boron nitride, 8 parts by mass of nano-silicon nitride, 2 parts by mass of silane coupling agent KH-570 and 2000 parts by mass of water were added to a reaction flask and mixed, dried at 90 ° C for 3 hours, and the water was removed to obtain a modified inorganic powder;
[0060] S2. 100 parts by mass of epoxy resin was added to the reaction flask and stirred, heated to 100 ° C, 35 parts by mass of modified inorganic powder was added in 5 batches, degassed at 135 ° C, 0.2kPa until no bubbles were released, the vacuum was released and the temperature was lowered to 100 ° C, 40 parts by mass of hexahydrophthalic anhydride and 15 parts by mass of acetylacetonate iron were added, heated to 110 ° C, cured for 5 hours, cooled and removed to obtain a high thermal conductivity epoxy resin composite;
[0061] The prismatic aluminum oxide has an edge length of 1 to 15 μm and a bottom side length of 100 to 500 nm. The prismatic aluminum oxide is filled in a staggered manner in the pores. The diameter of the flake boron nitride is 0.8 to 1.2 μm. The diameter of the nano silicon nitride is 10 to 20 nm.
[0062] Comparative Example 3
[0063] This comparative example provides a method for preparing a high thermal conductivity epoxy resin composite, comprising the following steps:
[0064] S1. 33 parts by mass of prismatic alumina, 2 parts by mass of silane coupling agent KH-570 and 2000 parts by mass of water were added to a reaction flask and mixed, dried at 90 ° C for 3 hours, and water was removed to obtain a modified inorganic powder;
[0065] S2. 100 parts by mass of epoxy resin was added to the reaction flask and stirred, heated to 100 ° C, 35 parts by mass of modified inorganic powder was added in 5 batches, degassed at 135 ° C, 0.2kPa until no bubbles were released, the vacuum was released and the temperature was lowered to 100 ° C, 40 parts by mass of hexahydrophthalic anhydride and 15 parts by mass of acetylacetonate iron were added, heated to 110 ° C, cured for 5 hours, cooled and removed to obtain a high thermal conductivity epoxy resin composite;
[0066] The prismatic aluminum oxide has an edge length of 1 to 15 μm, a bottom side length of 100 to 500 nm, and the prismatic aluminum oxide is filled in a staggered manner in the pores.
[0067] Comparative Example 4
[0068] This comparative example provides a method for preparing a high thermal conductivity epoxy resin composite, comprising the following steps:
[0069] S1. 33 parts by mass of boron nitride flakes having a diameter of 20 to 100 nm, 2 parts by mass of a silane coupling agent KH-570 and 2000 parts by mass of water were added to a reaction flask and mixed, dried at 90 ° C for 3 hours, and water was removed to obtain a modified inorganic powder;
[0070] S2. Add 100 parts by mass of epoxy resin into a reaction bottle and stir, heat to 100°C, add 35 parts by mass of modified inorganic powder in 5 batches, degas at 135°C and 0.2kPa until no bubbles are released, release the vacuum and cool to 100°C, add 40 parts by mass of hexahydrophthalic anhydride and 15 parts by mass of acetylacetonate iron, heat to 110°C, cure for 5 hours, take out after cooling, and obtain a high thermal conductivity epoxy resin composite.
[0071] Comparative Example 5
[0072] This comparative example provides a method for preparing a high thermal conductivity epoxy resin composite, comprising the following steps:
[0073] S1. 33 parts by mass of nano-silicon nitride having a diameter of 10 to 20 nm, 2 parts by mass of a silane coupling agent KH-570 and 2000 parts by mass of water were added to a reaction flask and mixed, dried at 90 ° C for 3 hours, and water was removed to obtain a modified inorganic powder;
[0074] S2. Add 100 parts by mass of epoxy resin into a reaction bottle and stir, heat to 100°C, add 35 parts by mass of modified inorganic powder in 5 batches, degas at 135°C and 0.2kPa until no bubbles are released, release the vacuum and cool to 100°C, add 40 parts by mass of hexahydrophthalic anhydride and 15 parts by mass of acetylacetonate iron, heat to 110°C, cure for 5 hours, take out after cooling, and obtain a high thermal conductivity epoxy resin composite.
[0075] Performance Test:
[0076] The thermal conductivity of the cured products of the high thermal conductive epoxy resin composites of Examples 1 to 5 and Comparative Examples 1 to 5 was measured according to GB / T 29313-2012 at 105° C. The impact strength was measured by the simply supported beam method according to GB / T 1043.1-2008, and the specimens had no notches.
[0077] Table 1. High thermal conductivity epoxy resin composites of Examples 1 to 4 and Comparative Examples 1 to 6.
[0078] sample Thermal conductivity (W / (m·K)) <![CDATA[Impact strength (kJ / m 2 )]]> Example 1 1.84 18 Example 2 1.87 17 Example 3 1.86 16 Example 4 2.03 17 Example 5 1.69 10 Comparative Example 1 1.31 16 Comparative Example 2 1.40 17 Comparative Example 3 1.29 15 Comparative Example 4 1.25 17 Comparative Example 5 1.22 16
[0079] It can be seen from Table 1 that the high thermal conductivity epoxy resin composite prepared in the present invention has high thermal conductivity and high impact strength.
[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that after reading the specification of this application, the technicians can still modify or replace the specific implementation mode of the present invention with equivalents, but these modifications or changes do not deviate from the scope of protection of the pending claims of the present application.
Claims
1. A method for preparing an epoxy resin composite, characterized in that: The steps include: S1. 15 to 19 parts by mass of prismatic alumina, 7 to 9 parts by mass of flake boron nitride, 7 to 9 parts by mass of nano silicon nitride, 1 to 3 parts by mass of a silane coupling agent and water are mixed and dried to obtain a modified inorganic powder; S2. 100 parts by mass of epoxy resin, 0 to 10 parts by mass of colorant were mixed, heated with stirring, 30 to 40 parts by mass of modified inorganic powder were added in batches, deaerated, 30 to 50 parts by mass of anhydride curing agent and 10 to 20 parts by mass of curing accelerator were added, heated and cured to obtain an epoxy resin composite; The prismatic aluminum oxide has an edge length of 1-15 μm and a bottom side length of 100-500 nm. The prismatic aluminum oxide is filled in a staggered manner in the pores. The diameter of the flake boron nitride is 20-100 nm. The diameter of the nano silicon nitride is 10-20 nm.
2. The method for preparing the epoxy resin composite according to claim 1, characterized in that: In S1, the silane coupling agent includes at least one of KH-570, KH-550, KH-560, and KH-590.
3. The method for preparing the epoxy resin composite according to claim 1, characterized in that: In S1, the drying temperature is 85-90° C. and the drying time is 3-5 hours.
4. The method for preparing the epoxy resin composite according to claim 1, characterized in that: In S2, the temperature of the heating and stirring is 90-110°C.
5. The method for preparing the epoxy resin composite according to claim 1, characterized in that: In S2, the batching is divided into 3 to 6 batches.
6. The method for preparing the epoxy resin composite according to claim 1, characterized in that: In S2, the degassing temperature is 130-140°C and the pressure is 0.1-0.3 kPa.
7. The method for preparing the epoxy resin composite according to claim 1, characterized in that: In S2, the anhydride curing agent includes at least one of hexahydrophthalic anhydride, nadic anhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic anhydride, cyclobutanetetracarboxylic anhydride, methyltetrahydrophthalic anhydride, methylendomethylenetetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, tetrahydrophthalic anhydride, and 3,3'-dithiodipropionic anhydride.
8. The method for preparing the epoxy resin composite according to claim 7, characterized in that: The acid anhydride curing agent is selected from at least one of 4-methyltetrahydrophthalic anhydride, 3-methyltetrahydrophthalic anhydride and 4-methylhexahydrophthalic anhydride.
9. The method for preparing the epoxy resin composite according to claim 7, characterized in that: The acid anhydride curing agent is selected from 3,3'-dithiodipropionic anhydride.
10. The method for preparing the epoxy resin composite according to claim 1, characterized in that: In S2, the curing accelerator includes at least one of iron acetylacetonate, copper acetylacetonate, and zinc acetylacetonate.
11. The method for preparing the epoxy resin composite according to claim 1, characterized in that: In S2, the temperature of the heating and curing is 70-120° C., and the time is 0.5-5 hours.
Citation Information
Patent Citations
Ultrahigh-heat-conducting insulating epoxy resin material and preparation method thereof
CN113549301A